"Stop anxiety": contributions to the development of a system to manage anxiety in newcomers - Silva, Pedro Miguel Marques (2020)
Mental health problems have a significant impact on quality of life. The epidemiological prevalence of anxiety among college students hinders accurate treatment among universities health centers. Therefore, it subsists a need to explore new preventive ways, avoiding, the engagement in therapies. Mobile health (m-health) technologies emerge as an accessible and ubiquitous way to deliver psychological therapies that support users in the management of health-related problems, in this case mental health problems. However, many of the available tools do not provide evidence-based support of the adequateness and effectiveness of techniques used. Moreover, most tools are designed without considering the users' needs and motivations, resulting in poor adherence or lack of motivation for systematic use of these tools, hindering the efficacy of the techniques it uses. Bearing in mind the need to consider the motivations of the target users, this study exposes the efforts of a multidisciplinary team in developing and designing a tool to support anxiety management in the academic campus resorting to a user-centered approach. In this sense, this paper presents the description of the target population, in this case newcomers, in order to develop a system capable of assisting these first-year students in the difficulties experienced in the management of anxiety and stress arising from the various academic contexts.